Optimizing outcomes when treating functional neurological disorder in acute care settings: case reports depicting the value of diagnostic precision and timely and appropriate psychological interventions using an interdisciplinary framework - Greenfield, Melissa J.; Fobian, Aaron D.; Fargason, Rachel E.; Birur, Badari (Frontiers in Psychiatry, 2024)
Introduction Unexplained physical signs and symptoms represent a significant portion of patient presentations in acute care settings. Even in cases where a patient presents with a known medical condition, functional or somatic symptoms may complicate the diagnostic and treatment processes and prognostic outcome. One umbrella category for neurologically related somatic symptoms, functional neurological disorder (FND), presents as involuntary neurological symptoms incompatible with another medical condition. Symptoms may include weakness and/or paralysis, movement disorders, non-epileptic seizures, speech or visual impairment, swallowing difficulty, sensory disturbances, or cognitive symptoms (1). While FND presents as neuropsychiatric, providers commonly report feeling hesitant to diagnose these disorders. Inexperience or lack of appropriate education on relevant research regarding evidence-based practices or standard of practice (SOP) may result in over- or underperforming diagnostic workups and consultations, utilizing inappropriate medications, and failing to offer evidence-based psychological interventions. Being mindful of these challenges when treating patients presenting with functional symptoms in acute care settings can help to support and protect the patients and care team and appropriately control healthcare costs. Methods The University of Alabama at Birmingham Medical Center identified cases representing categories of quality and safety problems that arise in treating FND in acute care settings. Patients signed a consent form to participate in the case report. The case information for each was presented without identifying information. Discussion The cases highlight potential challenges when caring for patients presenting with FND in acute care settings. The challenges covered include over- or underutilization of diagnostic workups and consultation, over- or underutilization of psychopharmacological medications, and over- or undertreating a medical condition when a functional symptom is present. In each case, these lapses and errors caused the patient distress, additional treatments, care delays, and delayed symptom remission. Additionally, these challenges have direct and indirect fiscal costs, which can be mitigated with the appropriate education and training, resources, and protocols. Hospitals can benefit from system-wide SOP to improve the identification and management of FND to prevent harm to patients. An SOP commonly presents to specific specialties and ensures the appropriate diagnostic workup, consultations, and timely evidence-based interventions.